IMPLEMENTASI FOOD SAFETY DALAM MENINGKATKAN KUALITAS PRODUK KULINER DI JAMBULUWUK OCEANO SEMINYAK HOTEL - Kadek Ananda Hary Krishna; I Gede Putra Nugraha; Luh Putu Triyanti Ariestiana Dewi (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
This study aims to analyze the implementation of food safety to improve the quality of culinary products at the Jambuluwuk Oceano Seminyak Hotel and identify inhibiting factors. The study employed a qualitative descriptive approach with a case study method. Data collection included direct observation in the kitchen and restaurant areas, in-depth interviews with the Executive Chef, Food and Beverage Product staff, stewards, and daily workers, as well as documentation in the form of Standard Operating Procedures (SOPs), photographs of operational activities, and other supporting records. The results indicate that food safety implementation at the Jambuluwuk Oceano Seminyak Hotel has been implemented throughout all stages of kitchen operations, including receiving and storing raw materials, processing, and serving food, adhering to the principles of hygiene, sanitation, and the HACCP system. This implementation has contributed positively to the consistency of the quality, safety, and quality of culinary products served to guests. However, several inhibiting factors were identified, including varying levels of employee knowledge and compliance with food safety standards, limited human resources, and increased workloads during peak operating hours. Therefore, enhanced training, ongoing supervision, and management commitment are needed to optimally improve the effectiveness of food safety implementation.